2004
DOI: 10.12968/bjon.2004.13.9.12972
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted lives: investigating coping strategies for non-healing leg ulcers

Abstract: The aim of this study was to explore the lived experience of people who have non-healing venous ulcers using hermeneutic phenomenology. Unstructured interviews were carried out with five people who also completed a diary. Interpretative phenomenological analysis was utilized to identify themes and patterns. The core themes identified through analysis were biographical disruption, ways of coping, social implications and therapeutic relationships. The emergent themes reveal the impact of chronicity in participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 35 publications
0
70
0
4
Order By: Relevance
“…7,44,45 Pain was overwhelming, incessant and unrelenting; it had profound effects on the patient, impacting on their sleep, mobility and day-to-day functioning and was exacerbated by both dressings and treatment regimens. 10,[47][48] Pain, for some, was a 'constant companion', it persistently reminded them of the unremitting nature of their ulceration, [47][48][49] controlling their existence and making them angry, sad and 'to cry in despair'. 50,p.239 The control of pain was also problematic; 45,47,48,51 respondents often under-reported pain 47,48 and were reluctant to take analgesia which was deemed ineffective.…”
Section: Painmentioning
confidence: 99%
See 2 more Smart Citations
“…7,44,45 Pain was overwhelming, incessant and unrelenting; it had profound effects on the patient, impacting on their sleep, mobility and day-to-day functioning and was exacerbated by both dressings and treatment regimens. 10,[47][48] Pain, for some, was a 'constant companion', it persistently reminded them of the unremitting nature of their ulceration, [47][48][49] controlling their existence and making them angry, sad and 'to cry in despair'. 50,p.239 The control of pain was also problematic; 45,47,48,51 respondents often under-reported pain 47,48 and were reluctant to take analgesia which was deemed ineffective.…”
Section: Painmentioning
confidence: 99%
“…Eight of the eleven studies referred to issues due to leakage from the wound and the associated malodour 10,11,45,[47][48][49][50][51] Exudate was unbearable and devastating, 11 with the unpredictability of dressing leakage causing distress and shame. 51 There were reports of wet shoes, wet bedding and concerns of what people might think.…”
Section: Exudate and Odourmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, the concept may not be applicable to those who have always lived with general adversity and material deprivation or who anticipate ill health because of their circumstances, perceived life expectancy or life stage expectation and age. For these individuals, the onset of chronic illness is just another facet of a 'hard life' which may even be biographically anticipated and therefore not amounting to a fundamental and profound biographical disruption but rather one of continuity and normality (Faircloth et al, 2004;Hopkins, 2004;Leveälahti, Tishelman, and Ohlén, 2007;Pound, Gompertz, and Ebrahim, 1998;Richardson, Ong, and Sim, 2006). A study of older women diagnosed with cancer, however, cautions against assuming that those with hard and long lives do not experience cancer as biographical disruption (Sinding and Wiernikowski, 2008).…”
Section: The Importance Of Contextmentioning
confidence: 99%
“…The psychological stress that can be associated with malodorous wounds and negative effect on wound healing has been identified [3,4], with some tentative links established between exudate, and associated odour with depression and anxiety [5]. Malodorous leg ulcers have been reported to have a negative effect on patients' social lives [6,7] leading to higher anxiety and depression scores, lower life satisfaction and altered body image [8]. Bland [9] reported that patients were often embarrassed about the smell of their leg ulcer and thus did not leave the house with this being aggravated by the fact that bandaging on the leg prevented regular showers being taken.…”
Section: Introductionmentioning
confidence: 99%